Infection of groundnut ringspot virus in Plumeria pudica characterized by irregular virus distribution and intermittent expression of symptoms - Favara, Gabriel Madoglio; Oliveira, Felipe Franco de; Ferro, Camila Geovana; Kraide, Heron Delgado; Carmo, Eike Yudi Nishimura; Bello, Vinicius Henrique; Ribeiro-Junior, Marcos Roberto; Krause-Sakate, Renate; Kitajima, Elliot Watanabe; Rezende, Jorge Alberto Marques (Frontiers in Plant Science, 2023)
Plumeria pudica, known as bridal bouquet, exhibiting characteristic symptoms of orthotospovirus infection were found in different localities in Brazil. Symptoms were restricted to leaves of the middle and lower thirds of a few branches of each plant. Electron microscopy, molecular analyses, and complete genome sequencing identified the orthotospovirus as groundnut ringspot virus (GRSV),member of the species Orthotospovirus arachianuli. The virus was poorly transmitted mechanically to P. pudica. Reverse transcription polymerase chain reaction (RT-PCR) and reverse transcription quantitative polymerase chain reaction (RT-qPCR) analyses performed using total RNA extracted from leaf blades, primary veins, petioles, and regions of petiole insertion on branches indicated the presence of GRSV, predominantly in the symptomatic leaf blades. Symptomatic branches propagate vegetatively, often resulting in plants expressing GRSV symptoms. In contrast, vegetative propagation of the asymptomatic branches of infected plants predominantly generates plants without GRSV symptoms. The resistance of P. pudica plants to GRSV infection, restricted systemic viral movement, and expression of symptoms in infected plants suggest that this orthotospovirus does not threaten this ornamental plant.